2021
DOI: 10.3390/nu13114174
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SARS-CoV-2 Lockdown on Anthropometric Parameters in Children 11/12 Years Old

Abstract: Background: During the great lockdown in Spain due to SARS-CoV-2, in between the months of March and June 2020, dietary and physical activity habits were modified in children. The aim of the study was to determine the impact of the lockdown on anthropometric parameters in children aged 11/12 years. Methods: Fifty Spanish children aged 11/12 years (M = 11.40; SD = 0.50) participated: 33 (66%) boys and 17 (34%) girls. For data collection, we used an anthropometry kit; the Alpha-Fitness Battery, a validated instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 32 publications
(37 reference statements)
2
26
0
Order By: Relevance
“…One of the anthropometric measures that was found to be unaffected was WC, with no significant changes when comparing pre-lockdown and lockdown values in both sexes. The above is in agreement with the study by Ramos-Alvarez et al [ 34 ] in a sample of Spanish children assessed during the pandemic in Spain. BMI results in this study showed increases in the indicator but without significant differences.…”
Section: Discussionsupporting
confidence: 93%
“…One of the anthropometric measures that was found to be unaffected was WC, with no significant changes when comparing pre-lockdown and lockdown values in both sexes. The above is in agreement with the study by Ramos-Alvarez et al [ 34 ] in a sample of Spanish children assessed during the pandemic in Spain. BMI results in this study showed increases in the indicator but without significant differences.…”
Section: Discussionsupporting
confidence: 93%
“…The WHO states that this segment of the population does not comply with the recommended time for them to lead an active and healthy life [ 36 , 45 ]. This fact has been accentuated in Spain as a consequence of the great lockdown of COVID-19, worsening the physical conditioning and anthropometric parameters of children and adolescents [ 4 , 5 , 45 , 46 ]. Manual dexterity is closely related to fitness levels [ 7 , 19 ], so this worsening may be one of the causes of the decrease in their manual dexterity values.…”
Section: Discussionmentioning
confidence: 99%
“…This measure resulted in changes in habits in the child and adolescent population, especially in terms of their time dedicated to daily physical activity (PA), time spent using screen devices and eating habits [ 2 , 3 , 4 ]. In addition, these changes in habits have resulted in changes in children’s anthropometric averages, physical condition and psychological and emotional states [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…BMI has also increased signi cantly during the pandemic and as a result, the number of overweight, obese, or extremely obese children has increased from 15.0-21.2%, representing a relative increase of 41.3%. In another longitudinal study, Ramos-Álvarez et al observed an increase in BMI and percentage of fat in children aged 11 and 12 years, with no change in WC values in the post-pandemic period [30]. These studies show that there is still no consensus in the literature regarding the worsening of anthropometric values.…”
Section: Discussionmentioning
confidence: 94%